2004
DOI: 10.1111/j.0958-7578.2004.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of von Willebrand factor antigen, von Willebrand factor‐cleaving protease and protein S in blood components used for treatment of thrombotic thrombocytopenic purpura

Abstract: Replacement of normal levels of von Willebrand factor-cleaving protease (VWF:CP, ADAMTS13) activity from infused plasma is important in plasma exchange (PEX) for the treatment of thrombotic thrombocytopenic purpura (TTP) patients. We have studied the VWF:CP activity, VWF multimer distribution, VWF:Ag, protein S (PS) activity and free PS antigen levels in fresh frozen plasma (FFP), cryosupernatant (CSP) and virally inactivated components treated with methylene blue/light (MB) or solvent detergent (SD) processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 28 publications
9
65
0
2
Order By: Relevance
“…10,11 ADAMTS13 activity was expressed as a percentage relative to the activity in pooled normal plasma (normal range 55%-126%; lower limit of detection 5%).…”
Section: Assaysmentioning
confidence: 99%
“…10,11 ADAMTS13 activity was expressed as a percentage relative to the activity in pooled normal plasma (normal range 55%-126%; lower limit of detection 5%).…”
Section: Assaysmentioning
confidence: 99%
“…However, large VWF multimers may continue to derive from endothelial cells, and cryoprecipitate-depleted plasma is comparable to fresh frozen plasma in the ADAMTS13 activity level [83][84][85]. Two small randomized controlled trials have failed to demonstrate that the use of cryoprecipitate-depleted plasma is superior to fresh frozen plasma as initial replacement therapy [86;87].…”
Section: Managementmentioning
confidence: 99%
“…The ADAMTS13 activity levels have been investigated in a variety of plasma products [83][84][85]. Levels comparable to that in fresh frozen plasma are present in various plasma fractions and some of its derived products.…”
Section: Managementmentioning
confidence: 99%
“…Garwood et al [6] have shown that, although a freeze-thaw step has little effect on fibrinogen and FVIII levels, losses due to MB treatment are 5-10% lower in fresh plasma compared to frozenthawed plasma. Other plasma factors like von WillebrandFactor, ADAMTS 13, AT, protein C and protein S, however, are only slightly or not at all affected [3,[7][8][9]]. The decrease in the level of fibrinogen is seen by the Clauss assay, but not in the antigen assay [9].…”
Section: Introductionmentioning
confidence: 99%